2013
DOI: 10.1111/chd.12064
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Nutritional Support and Malnutrition in Infants and Children with Congenital Heart Disease

Abstract: Although nearly half of the patients were malnourished at surgery, only two-thirds of their recommended caloric and protein requirements were provided by week 1. To improve hospital outcomes, care should be taken to optimize the nutritional condition of infants and children prior to and following surgical correction of congenital heart disease to improve hospital outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 42 publications
6
97
0
14
Order By: Relevance
“…Preoperative undernutrition has been associated with a decreased postoperative REE and increased hospital morbidity (38)(39)(40). Unfortunately, routine nutritional assessment was not completed on subjects prior to surgery and therefore could not be accounted for in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative undernutrition has been associated with a decreased postoperative REE and increased hospital morbidity (38)(39)(40). Unfortunately, routine nutritional assessment was not completed on subjects prior to surgery and therefore could not be accounted for in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…44 Both acute and chronic protein energy malnutrition states were prevalent (51.2% and 40.5%, respectively) in patients undergoing cardiac surgery and associated with longer hospital LOS. 45 A case-control study involving children (n ¼ 74) who have undergone open heart surgery showed that patients who died had progressively decreasing median weight-for-age Z score from birth, operation, and last recorded weight (0.12, À1.31, and À2.09, respectively) in comparison with the control group. 46 Those who had a drop in weight-for-age Z score >0.67 had increased odds of dying (OR 13.5, 95% CI: 3.6-51).…”
Section: Nutritional Status and Outcomes In Chdmentioning
confidence: 99%
“…On average, our malnourished patients tended to be extubated 12 hours after those counterpart patients with normal nutritional status; this is consistently reported in many different sets of patients. 5,[12][13][14] In comparison to our study, a study 14 investigated the influence of the nutritional status based on skinfold thickness, instead of weight for age. 14 According to the study, a lower total body fat mass, as well as acute and chronic malnourishment were associated with worse clinical outcome, assessed by the length of ICU stay, duration of mechanical ventilations, and duration of dopamine and milrinone infusion.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore even after surgery nutritional support plays an important role for improving outcome. 13 Most patients presenting late suffered from malnourishment due to relatively poor access to medical care in Indonesia, where waiting times for surgeries are often extended to months, well beyond Western standards. The only way to improve this is to improve access to care.…”
Section: Discussionmentioning
confidence: 99%